Identification of genetic locus with resistance to take-all in the wheat-Psathyrostachys huashanica Keng introgression line H148 - Sheng-sheng BAI; Han-bing ZHANG; Jing HAN; Jian-hui WU; Jia-chuang LI; Xing-xia GENG; Bo-ya LÜ; Song-feng XIE; De-jun HAN; Ji-xin ZHAO; Qun-hui YANG; Jun WU; et al. (Journal of Integrative Agriculture)
Take-all is a devastating soil-borne disease of wheat (Triticum aestivum L.). Cultivating resistant line is an important measure to control this disease. Psathyrostachys huashanica Keng is a valuable germplasm resource with high resistance to take-all. This study reported on a wheat-P. huashanica introgression line H148 with improved take-all resistance compared with its susceptible parent 7182. To elucidate the genetic mechanism of resistance in H148, the F2 genetic segregating population of H148×XN585 was constructed. The mixed genetic model analysis showed that the take-all resistance was controlled by two major genes with additive, dominant and epistasis effects. Bulked segregant analysis combined with wheat axiom 660K genotyping array analysis showed the polymorphic SNPs with take-all resistance from P. huashanica alien introgression were mainly distributed on the chromosome 2A. Genotyping of the F2 population using the KASP marker mapped a major QTL in an interval of 68.8–70.1 Mb on 2AS. Sixty-two genes were found in the target interval of the Chinese Spring reference genome sequence. According to the functional annotation of genes, two protein genes that can improve the systematic resistance of plant roots were predicted as candidate genes. The development of wheat-P. huashanica introgression line H148 and the resistant QTL mapping information are expected to provide some valuable references for the fine mapping of disease-resistance gene and development of take-all resistant varieties through molecular marker-assisted selection.